Oral cancer’s new enemy: Goniothalamus umbrosus targets oral squamous cell carcinoma and spare human gingival fibroblast cells - Che Aziz, Nuraini; Mustafa Al-Ahmad, Basma Ezzat; Kashmola, Muhanad Ali Hamdon; Lestari, Widya; Nik Mohd Rosdy, Nik Mohd Mazuan; Mokhtar@Makhtar, Khairani Idah (Georg Thieme Verlag, 2025)
Objective: Oral squamous cell carcinoma (OSCC) is the prevailing type of oral cancer, representing poor prognosis and elevated mortality rates. Major risk factors for OSCC include the use of tobacco products, alcohol consumption, betel quid chewing, and genetic mutation. Goniothalamus umbrosus is traditionally consumed by cancer patients to fight against tumor growth. To date, research on the anticancer potential of G. umbrosus in oral cancer remains deficient. This study aimed to evaluate the anticancer potential of G. umbrosus in OSCC cell lines (SCC-15 and HSC-3) and compare its cytotoxic activity on human gingival fibroblast (HGF) cell lines.